Dinâmica geoambiental da Praia de Bitupitá, Ceará, Brasil: processos morfo-sedimentares e meio ambiente litorâneo - Pereira, Bruno Gonçalves (2018)
In order to understand the form of production of the coastal city and the structured transformation in the natural environment from the processes of modernization of the territory, the beach of Bitupitá, in Barroquinha / CE, is placed as a theoretical-empirical object, to verify the remodeling of the resulting natural features of the establishment of the urban way of life, which has the consequence of the de-characterization of the natural landscapes under a dubious logic of urbanization. Sedimentological and cartographic interpretations are presented, presented in tables and flowcharts and a sequence of spatial approximations that seek to understand how the components of nature (natural dynamics) and the socio-spatial processes of formation and modernization of the territory are articulated for the production of the coastal environment. Through this study we seek to verify the effectiveness of an integrated, systemic approach based on a clear social context, where the process of territorial modernization will be the guiding thread to understand how the flows of matter and energy are changed in the coastal plain by social projects that are clearly strategies for the commodification of nature.